The Impact of Marketing Culture on Marketing Management Orientations - شبر ظافر عبد محمد; حسين انتصار عزيز (Journal of Economics and Administrative Sciences, 2016)
The problem of the study is concerned with the work of The Iraqi Airways Company in political, economic, and social environment that suffers instability for many years. This has its negative outcomes regarding its decisions of providing services to its markets and customers as a result of the orientations, behavior, and marketing values the company management adopted. The aim of this study is to investigate the marketing philosophy adopted by the management and to identify the extent it suits the materialistic and the human capacities of the company and its current environmental circumstances within the marketing culture common to the thoughts and behaviors of the management and their employees. And in order to achieve this aim the study develops a hypothetical pattern that limits the nature of the relationship between the dimensions of the marketing culture as an independent variable and the management orientations as an adopted variable. The hypotheses of the study are designed and tested by using advanced statistical instruments within the statistical program (Spass-22). The society of the study consists of (242) administrative and technical decision-makers. The questionnaire forms, as a main instrument of collecting data, are distributed to (150) manager, head of a department, and head of a section, beside the company data that support the questionnaire. The research reaches many conclusions the important of which are: 1.The management of the company are keen on applying the standards and values of the marketing culture through dimensions that are based on encouraging innovations, establishing personal communications and relationships and improving all types of its services to bring the customers’ opinions to the company’s interest in the near future. 2.The management focus on developing the currently served markets and consider serving new markets and providing various services later on. 3.The company management adopts in its current marketing orientations the philosophy of the orientation towards selling preferring it to other philosophies and orientations of marketing. This means that the company focuses more on its internal environment than on its external one. The study suggests many recommendations the important of which are: 1.The company should spread out the marketing culture among the employees through meetings, sessions, and activating the public relations in the company and reconsider their daily behavior to supervise the application of the values, beliefs and thoughts related to this culture. 2.The company should adopt the philosophy of orientation towards marketing and social marketing, which means to set out from the external environment to identify the needs and desires of the customers first and then providing the services that satisfy these needs and by so doing the company achieves the commitment to its social and moral responsibility